2019
DOI: 10.1103/physrevb.100.035204
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the high- TC ferromagnetic semiconductor (Ga,Fe)Sb: X-ray magnetic circular dichroism and resonance photoemission spectroscopy studies

Abstract: The electronic structure and the magnetism of the novel ferromagnetic semiconductor (Ga,Fe)Sb, whose Curie temperature T C can exceed room temperature, were investigated by means of x-ray absorption spectroscopy (XAS), x-ray magnetic circular dichroism (XMCD), and resonance photoemission spectroscopy (RPES). The line-shape analyses of the XAS and XMCD spectra suggest that the ferromagnetism is of intrinsic origin. The orbital magnetic moments deduced using XMCD sum rules were found to be large, indicating that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 65 publications
6
12
0
Order By: Relevance
“…The intermediate systems such as (Ga,Fe)As or (Al,Fe)Sb showed the total magnetic moment slightly smaller than 5 The orbital magnetic moment relative to the spin magnetic moment (m l /m s ) increases from 0.015 to 0.061 as a host semiconductor becomes heavier and spin-orbit interaction becomes stronger. This is consistent with the previous x-ray magnetic circular dichroism (XMCD) experiments, where m l /m s is 0.1 for (In,Fe)As [30] and 0.13 for (Ga,Fe)Sb [31].…”
Section: Resultssupporting
confidence: 93%
“…The intermediate systems such as (Ga,Fe)As or (Al,Fe)Sb showed the total magnetic moment slightly smaller than 5 The orbital magnetic moment relative to the spin magnetic moment (m l /m s ) increases from 0.015 to 0.061 as a host semiconductor becomes heavier and spin-orbit interaction becomes stronger. This is consistent with the previous x-ray magnetic circular dichroism (XMCD) experiments, where m l /m s is 0.1 for (In,Fe)As [30] and 0.13 for (Ga,Fe)Sb [31].…”
Section: Resultssupporting
confidence: 93%
“…Besides the main peak at ∼ 708 eV, there is a shoulder structure at ∼ 710 eV in the XAS spectra of (Ga,Fe)Sb. The previous XMCD and RPES studies 26 showed that the shoulder component can be attributed to Fe 3+ oxides (such as α-Fe2O3) and is not related to the ferromagnetism in (Ga1-x,Fex)Sb. The oxidized components in the present capped (Ga,Fe)Sb samples are less than that in a previous uncapped (Ga,Fe)Sb thin film 26 , suggesting that the surface of our samples is well protected by the amorphous Sb capping layer from oxidation.…”
Section: A Xas Spectra At the Fe L23 Absorption Edgementioning
confidence: 87%
“…To characterize the x dependence of the Fe-3d PDOS in the VB structure, we have conducted RPES measurements on the (Ga1-x,Fex)Sb (x = 0.05, 0.15, and 0.25) thin films and analyzed the spectra in detail. The resonant enhancement of the photoemission intensity measured at hν = 708 eV should reflect the energy position of the ferromagnetic component of Fe 3d states in (Ga1-x,Fex)Sb, because Fe L3 XMCD has a prominent peak at hν = 708 eV, the intensity of which as a function of magnetic field shows a ferromagnetic behavior 26 . Figure 2(a) shows the RPES spectra of the (Ga1-x,Fex)Sb thin films taken at hν = 708 eV (on-resonance) and hν = 704 eV (off-resonance), respectively.…”
Section: B Rpes: Comparison Between On-and Off-resonance Spectramentioning
confidence: 99%
See 2 more Smart Citations